Does hip flexor muscle weakness cause stiff-knee gait in long-term after medial open reduction surgery for children with developmental dislocation? - EVRENDILEK, HALENUR (My University, 2019)
Introduction Medial open reduction surgery (MOR) is performed as a treatment for children with developmental dislocation of the hip (DDH) by sectioning iliopsoas tendons [1]. A 10 years follow-up study of MOR was determined that hip flexor strength decreased in children with DDH [2] . Furthermore, the weakness of iliopsoas muscle was any one of the reasons of stiff knee gait pattern (SKG) [3], Therefore, the aim of the study was to determine whether the sagittal plane knee kinematics alters in long-term after bilateral MOR for children with DDH. Research Question What are the long-term biomechanical effects of bilateral MOR on sagittal plane knee kinematics in children with dislocation of the hip? Methods Five children (DDH group, 10 limbs, Av. age: 11.2 ± 2.8 y.o.) who had medial open reduction surgery bilaterally (10.4 years ago, Av. age: 9.6 ± 6 months o.) and six children without any orthopedic disorder (Control group, 12 limbs, Av. age: 10.8 ± 2.4 y.o) have participated in this study. All participants' selfselected speed of gait were analyzed by 3D gait analysis (BTS Bioengineering). The spatiotemporal parameters, sagittal plane hip and knee parameters and four defined SKG parameters (Pl: peak knee flexion angle, P2: range of knee flexion from toe-off to peak flexion, P3: total range of knee motion, P4: timing of peak knee flexion in swing, >3 significantly changed SKG parameters described as stiff knee ) [4] were examined. Independent t-test and Mann Whitney U test were used for comparison (p < 0.05) Results Between two groups, age, mean velocity were not significantly different (p>0.05). In DDH group, sagittal plane hip and knee range, P l, P2, P3,P4, maximum hip and knee flexion velocity were lower significantly than control group (Table 1). Discussion Normally, in late-stance, the iliopsoas is elongated depending on hip extension, then contracts at the beginning of the swing to initiate hip flexion. [5], Weakness of iliopsoas muscle, as a long-term effect of MOR surgery, reduces hip and knee flexion velocity at pre-swing and swing phases. This study showed that DDH altered all four SKG parameters significantly [4] relative to controls. This study also confirmed that hip flexion weakness may cause SKG pattern even neurologically intact individuals (3). Because of the SKG pattern increases not only the risk of reduced toe clearance and tripping but also energy expenditure [4], adding hip flexor strengthening exercises into rehabilitation programs might have a critical role for SKG treatment.